2021
DOI: 10.3389/fonc.2021.635537
|View full text |Cite
|
Sign up to set email alerts
|

The Clinicopathological Characteristics of Alpha-Fetoprotein-Producing Adenocarcinoma of the Gastrointestinal Tract—A Single-Center Retrospective Study

Abstract: Alpha-fetoprotein (AFP)-producing adenocarcinoma from the gastrointestinal tract (APA-GI) is a rare type of highly malignant tumor with a poor prognosis. It may originate from any site along the GI tract with similar clinicopathological characteristics. As limited research had ever described the characteristics of APA-GI, the present article intends to systemically investigate the clinicopathological characteristics of APA-GI from a single center's retrospective study to deepen the understanding of the disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…3,19 As a specific tumor biomarker, AFP is an oncofetal protein produced by the fetal liver, gastrointestinal cells, and yolk sac, and AFP is widely used in the diagnosis of yolk cyst tumors, hepatoblastomas, and HCC. 3,20 Recent studies have shown that AFP is also frequently highly-expressed in other human tumors, such as those of enteroblastic GC, colorectal cancer, gallbladder cancer, lung cancer, and ovarian cancer, of which GHAC is the most common. 6,21,22 Clinically, advanced GC patients with liver metastasis or chronic hepatitis B also have elevated serum AFP.…”
Section: Discussionmentioning
confidence: 99%
“…3,19 As a specific tumor biomarker, AFP is an oncofetal protein produced by the fetal liver, gastrointestinal cells, and yolk sac, and AFP is widely used in the diagnosis of yolk cyst tumors, hepatoblastomas, and HCC. 3,20 Recent studies have shown that AFP is also frequently highly-expressed in other human tumors, such as those of enteroblastic GC, colorectal cancer, gallbladder cancer, lung cancer, and ovarian cancer, of which GHAC is the most common. 6,21,22 Clinically, advanced GC patients with liver metastasis or chronic hepatitis B also have elevated serum AFP.…”
Section: Discussionmentioning
confidence: 99%
“…Some circRNAs can be expressed differently in tissues, although their serum levels are not significantly different. As in the case of alpha-fetoprotein in hepatocellular carcinoma, one of the most intensively studied cancer biomarkers [83], even though circRNA candidates are upregulated or downregulated in cancer tissues compared with non-cancer tissues, the difference between their plasma or serum levels in patients and healthy controls may not be apparent. These circRNAs are not suitable for diagnosing or predicting diseases in a non-invasive manner [51].…”
Section: Discussionmentioning
confidence: 99%
“… 26 Hepatoid adenocarcinoma is the main pathological feature of alpha‐fetoprotein (AFP) CRC. 27 In the view of our “conversion‐deterioration‐double mutation” theory, it can be explained that CSCs (regardless of origin from stem cells or de‐differentiation of CRC cells) undergo an aberrant differentiation process and produce hepatic‐cancer‐like CRC cells, and these cells share the feature of secreting AFP, thus expressing an AFP‐producing pattern. Morphologically, they look like hepatic cancer cells and can adapt to the liver microenvironment well; therefore, they are more prone to liver metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…AFP‐producing CRC has poor differentiation and shows aggressive biological behavior and worse prognosis than traditional CRC 26 . A high metastasis rate and liver metastasis are the main characteristics of AFP‐producing CRC at initial diagnosis, 27 and synchronous distant metastasis is commonly observed 26 . Hepatoid adenocarcinoma is the main pathological feature of alpha‐fetoprotein (AFP) CRC 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation